O TEMA “OBESIDADE” EM LIVROS DIDÁTICOS DE CIÊNCIAS DO ENSINO FUNDAMENTAL. - RIBEIRO, Uerlene do Rosário Garcês (2019)
Obesity has not always been seen as a social stigma. It was once regarded as a sign of beauty, prestige and wealth, and was often regarded as a symbol of health, strength and power. Obesity has undergone (and has been undergoing) significant changes in society, and this has changed the way we perceive the "fat", which was once appreciated and valued today is visibly rejected. As it is a biomedical and sociocultural phenomenon, it is important that it be problematized from analyzes that think about the subject in a plural and citizen way, especially in the educational field. Thus, this research aims to analyze the discourses on obesity present in elementary science textbooks approved by the 2017 National Textbook Program (PNLD) and used in public schools in the city of São Luís, Maranhão. And yet: Understand the idea of obesity in these books; and characterize the biomedical and sociocultural aspects of obesity in these books. The research is characterized as being of qualitative perspective and documentary nature. Science textbooks were acquired in three schools in Vila Palmeira neighborhood, totaling twelve books (three collections) from 6th to 9th grade. The books were analyzed from the perspective of Cultural Studies in Education and Content Analysis following the guidelines of Bardin (1977). Therefore, it was possible to identify that, among the collections under analysis, the book in which the research theme has been presented most frequently is the 8th grade book. In the three collections, this book (8th grade) has been bringing information about obesity from the knowledge related to food. Thus appear discourses that revolve around “healthy” and movement. However, there were also representations of obesity in the 9th grade books related to the issue of weight and movement indicating once again that such activity is fundamental to people's quality of life. Therefore, from these premises we built 9 (nine) categories of analysis. We consider, therefore, to be relevant to reflect on the ways of perceiving obesity in the contexts - historical, social, cultural, medical, biological and educational from the textbook, understanding that it is in this material that the student often finds theoretical support to carry out their school activities and meet their educational needs. Moreover, it is the most used resource by the teacher to subsidize his teaching work. Thus, it was possible to realize that obesity is still considered a social stigma. The way food content is presented in these textbooks says a lot about the bias that still exists about fat. On a more superficial look it is thought that there is no information on obesity. However, this apparent “saying nothing” says a lot, that is, there is still a very big aversion around obesity. Textbooks talk about obesity in a sanitized way.And so, they propose ways to incorporate preventive measures so that bodies conform to what is considered “normal”, currently accepted (and standard), that is, thin bodies.